Eponymous Entrepreneurs - Belenzon, Sharon; Chatterji, Aaron K.; Daley, Brendan (American Economic Review, 2017)
We demonstrate that eponymy—firms being named after their owners—is linked to superior firm performance, but is relatively uncommon (about 19 percent of firms in our data). We propose an explanation based on eponymy creating an association between the entrepreneur and her firm that increases the reputational benefits/costs of successful/unsuccessful outcomes. We develop a corresponding signaling model, which further predicts that these effects will be stronger for entrepreneurs with rarer names. We find support for the model's predictions using a unique panel dataset consisting of over 1.8 million firms. (JEL D82, L25, L26, M13)